Estructura y Aspectos Histofisiológicos de la Pared Arterial del Perro - Orsi, Antonio M. [UNESP]; Domeniconi, Raquel F. [UNESP]; de Mello, Josiane M.; Spilla, Caio S. G. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
This paper described the architecture of the dog aortic arterial wall focused in the ascendant; thoracic descendent, and abdominal parts of the aorta. Furthermore, in this study we analyzed the wall structure of the right external iliac artery and the left vertebral artery of dog aiming to compare their architectural patterns with the aortic wall mainly in abdominal aortic part, which was structured by a mixed muscular and connective matrix equilibrated elements. The variables analyzed were the thickness of each mural layer; the number of elastic lamellae, mainly localized into the medial layer structure, and the diameters of each aortic segment. The aortic structure showed a typical elastic pattern in the ascendant and descendant thoracic parts, but in its abdominal segment a lesser presence of elastic lamellae permitted to classify it with a mixed mural composition. The aortic segments mainly presented variable amounts of smooth muscle cells and connective matrix assuming a meshwork pattern. Furthermore, smooth muscle cells were seen intermingled with connective lamellae and fibers forming the complex meshwork related, which certainly helped to guarantee the aortic mural integrity during the aortic blood flow.
Structure and histophysiological considerations on the arterial wall of the dog
Keywords: Artery; Dog; Histophysiology; Mural structure